Microarray profile of the humoral immune response to influenza vaccination in breast cancer patients treated with chemotherapy. Issue 9 (1st March 2017) - Wumkes, M.L.; van der Velden, A.M.T.; de Bruin, E.; Meerveld-Eggink, A.; Koopmans, M.P.G.; Rimmelzwaan, G.F.; Rijkers, G.T.; Biesma, D.H.
Highlights: Patients on chemotherapy have an impaired response to influenza virus vaccination. The broadness of the humoral immune response was assessed by a protein microarray. Overall there was a broad serum antibody response to influenza virus vaccination. Abstract: Background: Patients treated with chemotherapy have an impaired response to influenza virus vaccination compared to healthy controls. Little is known about the broadness of the antibody response in these patients. Methods: Breast cancer patients on FEC (5-fluorouracil, epirubicin and cyclophosphamide) chemotherapy regimens were vaccinated with influenza virus vaccine. Sera were obtained before and three weeks after vaccination. In addition to the determination of virus-specific antibody titres by hemagglutination inhibition assay, the broadness of the response was assessed by the use of a protein microarray and baseline titres were compared with an age-matched reference group. Results: We included 38 breast cancer patients and found a wide variety in serum antibody response after vaccination. Patients with a history of influenza vaccination had higher pre-vaccination titres, which were comparable to the reference group. Increasing number of cycles of chemotherapy did not have a negative effect on influenza array antibody levels, nor on the HI antibody response. Conclusions: Overall there was a broad serum antibody response to the influenza virus vaccine in patients treated with chemotherapy for breast cancer.